MEMBANGUN SMS-GATEWAY UNTUK PENGISIAN PULSA ELEKTRONIK BERBASIS WEB - Abdiansah - (Jurnal Sistem Informasi, 2009)
SMS Gateway is a middleware that communicate between a computer and a handphone. SMS management has done with computer process. This research has implemented SMS gateway and used Gammu SMS gateway application in case study to charge pulse value in handphone via website. Thereby the transaction will be fast and efficient. Every transaction has done the system record transaction history into database. Also the system automatically generate report for administrator. Generally the system have three process for doing transaction: 1. Computer and handphone management 2. SMS management used web interface and 3. Log transaction report.Key words: SMS Gateway, Gammu, Middleware